Implementation and Consequences of the Rule of Law and Human Rights - Atma, Ignasius (PT FORMOSA CENDEKIA GLOBAL, 2024)
Examining how Indonesia is implementing human rights under the 1945 Constitution is the aim of this journal. Human rights are basic freedoms that are innate to all people, eternal, and unalienable. No one, not even the state apparatus and government, is allowed to deny, curtail, or take away a person's human rights. Through a number of legal measures, the state has also guaranteed the protection of human rights, as stated in various sections of the 1945 Constitution. Indonesia is required to respect the principles of human rights as stated in the 1945 Constitution as a legitimate state. The purpose of the theory used is to describe the problem's quality and explanation using a qualitative method approach. According to the analysis, Indonesia's implementation of human rights is firmly based on the 1945 Constitution and the Rule of Law, which is consistent with the country's goals as a formal legal state and suggests that the state is dedicated to upholding human rights. The 1945 Constitution states that every person has the right to bodily and spiritual well-being in addition to human rights in the social, political, economic, cultural, educational, and religious spheres.